2012
DOI: 10.1177/0095244312439446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of nano ZnO and conventional grade ZnO on the cross-linking densities of NR/BR and NR/SBR blends

Abstract: In this research, the effect of nano zinc oxide (ZnO) and conventional ZnO on cross-linking densities of natural rubber (NR)/butadiene rubber (BR) and NR/styrenebutadiene rubber (SBR) blends was investigated. The cross-linking densities of blends were determined using swelling behavior technique. Blends of NR/BR and NR/SBR with various concentrations ranging from 0.5 to 5 parts per 100 g of rubber (phr) of nano ZnO and ZnO were prepared. A sheet of each compound was prepared using compression molding method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, the increase in M H is attributed to surface area of ller particles that promote higher interaction between ller/matrix with increases stifness of the material [45].…”
Section: Composites Evaluationmentioning
confidence: 99%
“…Furthermore, the increase in M H is attributed to surface area of ller particles that promote higher interaction between ller/matrix with increases stifness of the material [45].…”
Section: Composites Evaluationmentioning
confidence: 99%
“…al. 10 argued that the incorporation of nano ZnO instead of conventional rubber grade ZnO resulted in an increase of the cross-linking density. Nano ZnO provides a more effective surface for the formation of accelerator-sulfur-ZnO complex.…”
Section: Measurements Of Particle Sizes Of Zno Andmentioning
confidence: 99%
“…Good dispersion has been achieved by applying ball-milling techniques [4][5][6][7] or high-frequency ultrasounds to homogenize and disrupt agglomerates when ceramic molecules are employed. 8 Other strategies like the use of nanomaterials for compounding [9][10] or the chemical modification of inorganic particles [11][12][13] have been introduced on NR research area but are being scarcely applied in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…This lead to many investigations to reduce or eliminate zinc oxide in rubber formulations. These mostly involved replacement of conventional ZnO by nano‐ZnO particles, zinc complexes, and other metal oxides . It was found that the nano‐ZnO at 0.3–3.0 phr loading in NR/BR/silica compounds showed superior cure characteristics and mechanical properties over the conventional rubber compound based on micro‐sized ZnO at 5 phr loading .…”
Section: Introductionmentioning
confidence: 99%